The Operating and Financing Environmental of Local Public Transport - Tóth, Szabolcs (International Journal of Engineering and Management Sciences, 2019)
In Hungary the financing of the local public transportation is becoming a great obligation for the public service providers. The institutional framework of the national segment is in line with the european standards, nevertheless based on the analysis of the revenues it is clear to see that the core problem is to be found in the hungarian compensation system. The free and reduced rate fares originating from the social fare subvention system need to be reviewed and the realistic adjustment of the price compensation is evitable, due to the fact that the volume of the state normative compensation is not able to reach the volume off loss in revenues in the local public transportation. The amount of compensation required by local governments is raising every year. Besides assuring the stable operation it is also important to maintain the high quality of services and improve the segment in order to raise the number of passangers.